Study on the driving mechanism and risk hedging effect of economic policy uncertainty on digital transformation of agricultural enterprises - Wang, Wenwen; Jia, Jingwen (Frontiers in Sustainable Food Systems, 2025)
Agriculture constitutes an essential cornerstone of national security. The digital transformation of agricultural enterprises is a pivotal driver in promoting agricultural modernization, enhancing industrial competitiveness, and ensuring food security. This paper examines the impact of economic policy uncertainty on the digital transformation of agricultural enterprises, drawing on data from China’s A-share listed agricultural companies from 2007 to 2022. The research results indicate that: (1) Economic policy uncertainty significantly accelerates the digital transformation process of agricultural enterprises. (2) Mechanistic analysis reveals that, when confronted with economic policy uncertainty, agricultural enterprises are compelled to pursue digital transformation to mitigate market shocks, which result from decreased levels of risk-taking and investment efficiency. (3) Further heterogeneity analysis demonstrates that agricultural enterprises that are strategically positioned, face stronger financing constraints, occupy leading firm status, and focus on agricultural services are more inclined to undergo digital transformation under economic policy uncertainty. (4) By elucidating the compelling effects of economic policy uncertainty on the digital transformation of agricultural enterprises, this study validates the rationale for these enterprises’ adoption of digital strategies to mitigate the adverse effects of declining risk-taking levels and investment efficiency. Importantly, while the empirical context is grounded in China, the mechanisms and heterogeneity patterns identified—such as risk mitigation, financing constraints, and strategic positioning—offer implications for agricultural sectors in other regions navigating similar economic policy uncertainties. Ultimately, the conclusions drawn from this research seek to provide innovative strategies for agricultural enterprises to navigate the uncertainties of the external economic environment.